MANAGEMENT OF FUNGAL DISEASES OF ONION ( ALLIUM CEPA L.) BY USING PLANT EXTRACT.: Life Science-Botany - K.N.GAIKWAD; U. JADHAV, SHOBHA; V.R.KAKULTE (International Journal of Life Science and Pharma Research, 2014)
Onion is a most Important Vegetable crop grown throughout the world. Onion suffers from pest and fungal diseases but the fungicides cause pollution and disturb microbial balance of the soil. Under integrated fungal disease management programme cost effective and eco- friendly component like plant extracts are used to control plant pathogens. Alternaria porri, Fusarium oxysporium, Stemphylium vesicarium are soil borne pathogens of onion. Effect of three different plant extract ( Lawsonia alba, Parthenium hysterophorus, Moringa oleifera) at five different concentration Viz, 10,25,50,75 and 100 percentage on these pathogens was studied by food poisoning techniquie. Lawsonia alba gave 88.88% growth of Alternaria porri at 10% extract concentration and 33.33% growth at 100% extract concentration. In parthenium hysterophorus. at 10% extract concentration 87.5% growth and at 100% extract concentration 20.83% growth of Stemphylium vesicarium was observed. Stemphylium vesicarium give good in inhibitory response as compared to Alternaria porri and Fusarium oxysporium . Moringa oleifera in 10% extract concentration 89.47% growth and in 100% extract concentration 47.36% growth of Stemphylium vesicarium was recorded. Stemphylium vesicarium give good inhibitory response as compared to Fusarium oxysporium.